Measuring the effect of borrowing on property investments / Muhamad Fadzrizal Ayub - Ayub, Muhamad Fadzrizal (2007)
The effect of borrowing on property investments has been continues to be an important topic. To assess whether borrowing has increased the return on equity is to contrast the return on the property investments with the loan interest rates. Whenever the return on the property is higher than the loan interest rates, there is positive leverage. That means; there is a relationship between return on property investments and loan interest rates. This study provides the investigation of the relationship between loan interest rate and return on property investments in Malaysia using Pearson's Correlation model and Single Regression model. The purpose of the study is to determine the correlation and the relationship between loan interest rate and return on property investments. Furthermore, it wants to identify the strength of the association between these two variables. In order to obtain better analysis, the data of loan interest rates and return on property investments in Malaysia were analyzed in time series of 6 years from 2001 until 2006.